2003
DOI: 10.1002/bjs.4086
|View full text |Cite
|
Sign up to set email alerts
|

Complications and functional outcome following artificial anal sphincter implantation (Br J Surg 2002; 89: 877-881)

Abstract: SirWe commend the authors for their objectivity. Infection, migration and erosion are well-documented serious complications of artificial anal sphincter implantation, yet may be relatively under-reported. It has long been our belief that any artificial devices or material brought into direct contact and completely encircling the bowel wall would eventually fail as a result of displacement and/or subsequent erosion. In this long-term study over three-quarters of the patients experienced postoperative complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This discrepancy can be accounted for by the fact that many patients underwent an additional procedure to an ESGN and the complication rates included those due to these additional procedures. Sacral nerve stimulation has far less complications but the patients in this study were far too impaired for sacral nerve stimulation and we feel that an artificial bowel sphincter is not an option owing to sepsis [16]. Although ESGN has a high morbidity this is still preferable for our well‐counselled patients desperate to avoid a stoma at all costs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This discrepancy can be accounted for by the fact that many patients underwent an additional procedure to an ESGN and the complication rates included those due to these additional procedures. Sacral nerve stimulation has far less complications but the patients in this study were far too impaired for sacral nerve stimulation and we feel that an artificial bowel sphincter is not an option owing to sepsis [16]. Although ESGN has a high morbidity this is still preferable for our well‐counselled patients desperate to avoid a stoma at all costs.…”
Section: Discussionmentioning
confidence: 98%
“…Longer‐term results have been disappointing [14] whilst a systematic review of an artificial bowel sphincter concluded that it is of uncertain benefit and may actually harm many patients [15]. It remains to be seen how long‐term function will be with such a device [16].…”
Section: Introductionmentioning
confidence: 99%